2019
DOI: 10.1508/cytologia.84.69
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype Investigations in Iranian <i>Scorzonera tortuosissima</i> and <i>S. intricata</i>, Asteraceae

Abstract: Somatic chromosomes of two Scorzonera species from subgenus Scorzonera, section Intricatae collected from four localities in southeast Iran were observed. In S. tortuosissima, 2n=28 was observed. S. intricata revealed two chromosome numbers of 2n=20 and 21. The chromosome numbers of 2n=21 had one B chromosome then the basic number is x=10 which is a new basic chromosome number for Scorzonera. Both species showed a predominance of metacentric chromosomes in each karyotype. The karyotype was formulated as 12m+2s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The basic chromosome numbers reported in Scorzonera are x= 6 and x= 7 , Winfield et al 2006, Ghasemi et al 2015. The basic number of x=10 reported in S. intricata is a rare number (Bordbar et al 2019). It seems this species is an autotriploid species with the chromosome number of 2n=3x =21, and the chromosome number of 2n=20 is due to an aneuploidy event which is normal in triploid species.…”
Section: Taxonmentioning
confidence: 85%
See 1 more Smart Citation
“…The basic chromosome numbers reported in Scorzonera are x= 6 and x= 7 , Winfield et al 2006, Ghasemi et al 2015. The basic number of x=10 reported in S. intricata is a rare number (Bordbar et al 2019). It seems this species is an autotriploid species with the chromosome number of 2n=3x =21, and the chromosome number of 2n=20 is due to an aneuploidy event which is normal in triploid species.…”
Section: Taxonmentioning
confidence: 85%
“…conducted the most comprehensive cytological study on Scorzonera and reported the karyotype analysis of 22 species as well as reviewed previous chromosome numbers mentioned in Scorzonera. Considering recent papers, chromosome numbers have been determined for 14 Iranian species , Ghasemi et al 2015, Bordbar et al 2019. Therefore, in cytogenetic terms, the species belonging to the Scorzonera have been insufficiently studied.…”
mentioning
confidence: 99%